Analisis Dampak Otomasi pada Cafe' Kopitani, Dau, Malang: Antara Dinamika Efisiensi atau Aspek Sosial - Susenohaji; Rifki Muhammad Bintang; Amelia Ika Pratiwi (Public Sphere Review, 2025)
The rapid development of digital technology has encouraged the culinary industry including cafés to adopt automation systems for ordering, payment, and operational management. However, evidence regarding the effectiveness of automation, particularly in small and medium-sized enterprises, remains mixed. This study aims to analyze the impact of automation on operations and customer experience at Café Kopitani in Dau, Malang. A qualitative case study approach was employed, with data collected through in-depth interviews with the owner, manager, employees, and customers, as well as direct observations of service workflows before and after automation. The findings reveal several positive impacts of automation, including improved operational efficiency, faster ordering and payment processes, fewer recording errors, and enhanced data-driven decision-making. Nonetheless, the study also identifies several drawbacks, such as the loss of warmth in social interactions, reduced service flexibility, diminished local cultural nuances, limited adaptability in daily menu adjustments, and fewer employment opportunities for local residents. Regular customers also experience emotional effects stemming from the reduced personal interaction that previously served as one of Kopitani’s strengths. Overall, the findings contribute valuable insights into the dynamics of automation in small-scale culinary businesses, particularly those operating in rural areas.